Are Teachers Ready for Digitalization? English Teachers’ Attitudes and Efforts in Enhancing Their Digital Competence - Nurholis, Dewi; Mirizon, Soni; Amrullah (LPPM Undiksha, 2025)
The lack of digital competence among some teachers negatively impacts their ability to manage classrooms effectively. This study aims to analyze English teachers' attitudes toward digital competence and the initiatives they undertake to improve these skills. The study employs a qualitative approach with an investigative narrative design. The Digital Competence Framework for Educators (DigCompEdu) is adopted as the foundation of the research. The subjects of the study are four English teachers. Data were collected through interviews and documentation, using questionnaires as the primary instrument. The data were analyzed using thematic analysis. The findings reveal that teachers demonstrate positive attitudes toward digital competence and the integration of technology in the classroom. They recognize the benefits of technology in enhancing student engagement, creativity, and understanding. Overall, the teachers' digital competence is assessed at the